Alien and native plant seed dispersal by vehicles. (13th October 2017) - Khan, I.; Navie, S.; George, D.; O'Donnell, C.; Adkins, S. W.
Abstract: Vehicles play a significant role in spreading plants, both in terms of quantity and quality (species). This study was conducted in Southeast Queensland to determine the role of utility vehicles in spreading seeds. These vehicles were found to carry up to 397 seeds per vehicle and in all four seasons of the year, with the majority of these species being alien to Australia and/or Queensland. The largest seed loads were found in autumn in this summer rainfall environment. Seeds were shown to attach to all parts of the vehicle, often in mud picked up from the ground, affixed directly to the engine or radiator, or carried into the cabin by the driver. Therefore, much of the seed load is to be found on the underside, on the back and front mudguards while smaller collections were found in the cabin, on the radiator and engine, and on the tyres. Fewer viable seeds were found on the engine, presumably as desiccation and heat contributed more to their death on this part of the vehicle. One method used to reduce weed seed spread by vehicles in Queensland is washing and vacuuming of vehicles. From the present study, these procedures would need to be applied to all parts of the vehicle and in all seasons of the year.